Gonadal development and spawning of Nemipterus furcosus in the Pahang coastal water - Rahman, Mohammad Mustafizur; Yunus, Kamaruzzaman (2015)
This study aimed to understand gonadal development and spawning of Nemipterus furcosus population in the coastal water of Pahang. For this study, monthly samples were collected from commercial fishing trawlers for a period of one year. The results showed that male threadfin bream was significantly more than female (c2 = 121.68; p<0.05). A negative allometric growth was observed from February until June, and September for female while in January, March until June, and November for male. The significantly (P<0.05) lowest mean condition factor was found in July (1.2559) and the highest in August (1.3917) for male while lowest in March (1.2503) and highest in August (1.3926) for female N. furcosus. Mean gonadosomatic index (GSI) of female was higher than male in all months. GSI of female N. furcosus was highest in June while male in November. GSI of female rapidly increased after December and reached at peak in June and decline after June. Histological observation of gonads also showed reasonably similar stages of maturation in male and female. It showed immature gonadal stage in October and November. They enter the maturing stage in December, January and February and mature in March. After the mature stage, their testes and ovaries enter the ripe and running stage in April, May, June and July. Then, the gonad spent in August and finally enters the resting stage in September. The spawning season of threadfin bream in Pahang coastal water was from January to August. Histological study indicated that the peak spawning season occurs from April to July. This study indicated that the histological study is very useful to understand the peak spawning period of fish. The results of the study will be useful for the management of juvenile and breeding N. furcosus stock.